Impaired Sensitivity to Thyroid Hormones Is Associated With Elevated Blood Glucose in Coronary Heart Disease - Yu, Lu; Li, Zhu; Yang, Rongrong; Pan, Guangwei; Cheng, Qi; He, Yuanyuan; Liu, Yijia; Liu, Fanfan; Ma, Mei; Yang, Tong; Wang, Yang; Su, Jinyu; et al. (Frontiers in Endocrinology, 2022)
Context Thyroid hormone influences glucose homeostasis through central and peripheral regulations. So far, the association between thyroid hormone sensitivity and elevated blood glucose (EBG) in patients with coronary heart disease (CHD) remains unknown. The purpose of this study is to investigate the association between thyroid hormone sensitivity and risk of EBG in patients with CHD, and to further explore their association in different genders and ages. Methods This large multicenter retrospective study included 30,244 CHD patients (aged from 30 to 80) between January 1, 2014 and September 30, 2020. The study calculated the parameters representing central and peripheral sensitivity to thyroid hormones. Central sensitivity to thyroid hormones was assessed by calculating the thyroid feedback quantile-based index (TFQI), thyroid stimulating hormone index (TSHI), and thyrotropin thyroxine resistance index (TT4RI), and peripheral sensitivity to thyroid hormones was evaluated by the ratio of FT3/FT4. Taking normal glucose tolerance (NGT) as a reference, the study used logistic regression to analyze the relationship between central and peripheral thyroid hormone sensitivity and EBG in CHD patients. Results Among the 30,244 participants, 15,493 (51.23%) had EBG. The risk of EBG was negatively correlated with TSHI (OR: 0.86; 95%CI: 0.85 to 0.87; P < 0.001), TT4RI (OR: 0.99; 95% CI: 0.99 to 0.99; P<0.001), TFQI (OR: 0.72; 95%CI: 0.70 to 0.73; P <0.001) and PTFQI (OR: 0.60; 95%CI: 0.58 to 0.61; P<0.001). Compared to males and people aged 60 and below, the OR value for EBG was lower in females and those aged over 60 years old. Conversely, EBG risk was positively correlated with FT3/FT4 (OR: 1.25; 95% CI: 1.24 to 1.26; P <0.001) and in the sex-categorized subgroups, males had higher OR values than females. Conclusions This study shows that the increase in central thyroid hormone sensitivity is associated with the reduced risk of EBG in CHD patients, among which females and people aged over 60 years old are at higher risk.